Application of molybdenum disulfide composite coating in surface protection of nuclear energy component in oxygen or argon

By depositing a titanium/molybdenum disulfide/silver gradient transition layer and a molybdenum disulfide/silver composite layer on the surface of the nuclear energy component, the problem of degradation of friction performance of the molybdenum disulfide-based coating under an oxidative atmosphere is solved, and low friction and low wear effects are achieved in an oxygen or argon environment.

CN119685778APending Publication Date: 2025-03-25NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI +1

Patent Information

Application Number
CN202411898857.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing molybdenum disulfide (MoS2)-based coatings have reduced frictional performance under an oxidative atmosphere and are sensitive to humidity, which limits their terrestrial applications.

Method used

The titanium transition layer, a titanium/molybdenum disulfide/silver gradient transition layer and a molybdenum disulfide/silver composite layer are deposited on the surface of nuclear energy components using non-equilibrium magnetron sputtering technology. The silver is evenly distributed in the form of nanoparticles to form a special nanoparticle structure.

Benefits of technology

In oxygen or argon environment, the coating exhibits low coefficient of friction and wear rates, achieving environmental adaptability and long life-reliable service of the molybdenum disulfide-based coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119685778A_ABST
    Figure CN119685778A_ABST
Patent Text Reader

Abstract

The invention discloses application of a molybdenum disulfide composite coating in surface protection of a nuclear component in oxygen or argon. The molybdenum disulfide composite coating comprises a titanium transition layer, a titanium / molybdenum disulfide / silver gradient transition layer and a molybdenum disulfide / silver composite layer which are sequentially stacked in the thickness direction of the molybdenum disulfide composite coating. Wherein silver in the molybdenum disulfide / silver composite layer is uniformly distributed in molybdenum disulfide in the form of nanoparticles. The molybdenum disulfide composite coating provided by the invention has good friction and wear performance in an oxygen environment or an argon environment, can continuously and stably operate, and can meet the service requirements of low friction and stable lubrication in the nuclear power industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of surface lubricating coating materials, and in particular relates to use of a molybdenum disulfide composite coating in surface protection of nuclear energy components in oxygen or argon. Background Art

[0002] Friction remains one of the main causes of energy loss in mechanical systems. Molybdenum disulfide (MoS2) has broad application prospects in aerospace, nuclear energy and other fields due to its unique structural characteristics and inherent weak van der Waals forces that lead to easy interlayer slip. With the development of industrial technology, MoS2-based coatings are facing increasingly harsh service conditions, including high temperature, variable environment, high load and high-speed applications. These coatings can also function under special atmosphere conditions, such as carbon dioxide, nitrogen, oxygen and argon. However, MoS2 is highly sensitive to humidity, and when exposed to atmospheric conditions, it tends to form oxides with poor lubricity, which greatly reduces its lubrication efficiency and limits its terrestrial applications, while greatly increasing transportation costs.

[0003] Studies have found that in an argon environment, molybdenum disulfide coatings generally have a lower friction coefficient. In this inert gas environment, molybdenum disulfide will not fail due to oxidation or chemical reactions. In an oxidizing atmosphere, molybdenum disulfide produces a large number of defects due to friction. These defects will serve as active sites for gas adsorption and reaction, resulting in the easy generation of oxides at the sliding interface, which greatly reduces the tribological properties. Silver (Ag) is a soft metal known for its high fluidity and mechanical flexibility. It is usually used as a functional factor dopant to improve the environmental adaptability and tribological properties of MoS2. The patent with publication number CN112210753A discloses a molybdenum disulfide doped silver sulfide coating and its preparation method and application, wherein a titanium transition layer, a titanium / silver / molybdenum disulfide multilayer gradient transition layer and a molybdenum disulfide / silver doped sulfide layer are sequentially deposited on the surface of a substrate by magnetron sputtering technology, and then the obtained composite coating is subjected to high-temperature sulfidation treatment in a vacuum inert atmosphere to obtain the molybdenum disulfide doped silver sulfide coating. The molybdenum disulfide silver composite coating annealed in a high-temperature sulfur atmosphere of the application has good friction and wear properties in vacuum and atmospheric environments. However, since no special nanoparticle structure is formed in the molybdenum disulfide silver composite coating, it is difficult to form a dense transfer film in an oxidizing atmosphere, and thus the purpose of reducing friction and wear cannot be achieved. Summary of the invention

[0004] The main purpose of the present invention is to provide a molybdenum disulfide composite coating for use in the surface protection of nuclear energy components in oxygen or argon to overcome the shortcomings of the prior art.

[0005] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:

[0006] An embodiment of the present invention provides the use of a molybdenum disulfide composite coating in the surface protection of nuclear energy components in oxygen or argon, wherein the molybdenum disulfide composite coating comprises a titanium transition layer, a titanium / molybdenum disulfide / silver gradient transition layer and a molybdenum disulfide / silver composite layer stacked in sequence in the thickness direction of the molybdenum disulfide composite coating; wherein silver in the molybdenum disulfide / silver composite layer is uniformly distributed in the molybdenum disulfide in the form of nanoparticles.

[0007] An embodiment of the present invention also provides a molybdenum disulfide composite coating, which includes a titanium transition layer, a titanium / molybdenum disulfide / silver gradient transition layer and a molybdenum disulfide / silver composite layer stacked in sequence in the thickness direction of the molybdenum disulfide composite coating; wherein, in the molybdenum disulfide / silver composite layer, silver is uniformly distributed in the molybdenum disulfide in the form of nanoparticles.

[0008] An embodiment of the present invention also provides a method for preparing the aforementioned molybdenum disulfide composite coating, which comprises: using an unbalanced magnetron sputtering technology in combination with a six-target co-sputtering technology to sequentially deposit a titanium transition layer, a titanium / molybdenum disulfide / silver gradient transition layer and a molybdenum disulfide / silver composite layer on the surface of a nuclear energy component as a substrate, thereby forming a molybdenum disulfide composite coating; wherein the target materials used in the six-target co-sputtering technology include a silver target, two molybdenum disulfide targets, a titanium target and two molybdenum disulfide targets arranged in sequence in a counterclockwise direction, and the rotation speed of the sample holder fixing the nuclear energy component during the deposition of the molybdenum disulfide composite coating is 5 rpm.

[0009] Compared with the prior art, the present invention has the following beneficial effects:

[0010] (1) The molybdenum disulfide composite coating provided by the present invention has good friction and wear performance in a 100 mbar oxygen environment and a 100 mbar argon environment, and can meet the service requirements of low friction and stable lubrication of nuclear power bearings;

[0011] (2) The present invention can generate uniformly distributed 10-200 nm soft metal silver nanoparticles in the coating by controlling the rotation speed during the deposition process to 5 rpm. This special size of particle structure combined with the good self-lubricating properties and excellent wear resistance of molybdenum disulfide itself enables the silver nanoparticles in the coating to act as a binder in the molybdenum disulfide matrix and form a special "brick-mud structure" transfer film with metal oxide particles at the friction interface under harsh oxidizing atmosphere. The transfer film has a stable structure and can effectively reduce friction and wear. In addition, in an argon atmosphere, soft metal silver can effectively repair damaged surfaces and reduce wear; based on this, the obtained molybdenum disulfide / silver composite coating exhibits a low friction coefficient and wear rate under special atmospheres, realizing the environmental adaptability of the molybdenum disulfide-based coating. Therefore, compared with the prior art, the molybdenum disulfide / silver composite coating can better meet the long-life and reliable service of nuclear power bearings in harsh environments.

[0012] (3) The preparation method of the composite coating provided by the present invention is green, economical, controllable, and suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0014] Figure 1 1 is an XRD diagram of the MoS2 / Ag composite coating prepared in Example 1 of the present invention and the MoS2 coating prepared in Comparative Example 1;

[0015] Figure 2 is a cross-sectional SEM image of the MoS2 / Ag composite coating prepared in Example 1 of the present invention;

[0016] Figure 3 is a surface SEM image of the MoS2 / Ag composite coating prepared in Example 1 of the present invention;

[0017] Figure 4 is a structural TEM image of the MoS2 / Ag composite coating prepared in Example 1 of the present invention;

[0018] Figure 5 is a cross-sectional SEM image of the MoS2 coating prepared in Comparative Example 1 of the present invention;

[0019] Figure 6 is a surface SEM image of the MoS2 coating prepared in Comparative Example 1 of the present invention;

[0020] Figure 7 is a friction coefficient curve of the MoS2 / Ag composite coating prepared in Example 1 of the present invention in an oxygen environment of 100 mbar;

[0021] Figure 8 It is a friction coefficient curve of the MoS2 / Ag composite coating prepared in Example 1 of the present invention in an argon environment of 100 mbar. DETAILED DESCRIPTION

[0022] In view of the defects of the prior art, the inventor of this case has proposed the technical solution of the present invention after long-term research and extensive practice. The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] Specifically, as one aspect of the technical solution of the present invention, it involves the use of a molybdenum disulfide composite coating in the surface protection of nuclear energy components in oxygen or argon, wherein the molybdenum disulfide composite coating includes a titanium transition layer, a titanium / molybdenum disulfide / silver gradient transition layer and a molybdenum disulfide / silver composite layer stacked in sequence in the thickness direction of the molybdenum disulfide composite coating; wherein the silver in the molybdenum disulfide / silver composite layer is uniformly distributed in the molybdenum disulfide in the form of nanoparticles.

[0024] The molybdenum disulfide composite coating prepared by the present invention controls the rotation speed during the deposition process to be 5 rpm, so that the soft metal silver is evenly distributed in the coating in the form of nanoparticles of 10 to 200 nm. Therefore, in a harsh oxidizing atmosphere, the silver nanoparticles in the coating act as a binder in the molybdenum disulfide matrix and form a special "brick-mud structure" transfer film with metal oxide particles at the friction interface. The transfer film has a dense structure and can effectively reduce friction and wear in combination with the lubrication performance of molybdenum disulfide itself. In addition, the soft metal silver can effectively repair the damaged surface in an argon atmosphere to reduce wear.

[0025] In some preferred embodiments, in a direction gradually moving away from the titanium transition layer, the titanium content in the titanium / molybdenum disulfide / silver gradient transition layer gradually decreases, the molybdenum disulfide content gradually increases, and the silver content gradually increases.

[0026] In some preferred embodiments, the silver in the molybdenum disulfide / silver composite layer is uniformly distributed in the molybdenum disulfide in the form of nanoparticles with a particle size of 10 to 200 nm.

[0027] In some preferred embodiments, the atomic content of silver in the molybdenum disulfide / silver composite layer is 4 to 8 at %.

[0028] In some preferred embodiments, the thickness of the molybdenum disulfide composite coating is 1.9 to 3.2 μm.

[0029] In some preferred embodiments, the thickness of the titanium transition layer is 100-300 nm.

[0030] In some preferred embodiments, the thickness of the titanium / molybdenum disulfide / silver gradient transition layer is 100-400 nm.

[0031] In some preferred embodiments, the thickness of the molybdenum disulfide / silver composite layer is 1.7-2.5 μm.

[0032] In some preferred embodiments, the molybdenum disulfide composite coating has an average friction coefficient of less than 0.03 and a wear rate of less than 2×10 -7 mm 3 / N·m.

[0033] In some preferred embodiments, the average friction coefficient of the molybdenum disulfide composite coating in an argon environment of 100 mbar is less than 0.065, and the wear rate is less than 2.1×10 -7 mm 3 / N·m.

[0034] In some preferred embodiments, the preparation method of the molybdenum disulfide composite coating includes: using unbalanced magnetron sputtering technology in combination with six-target co-sputtering technology to deposit a titanium transition layer, a titanium / molybdenum disulfide / silver gradient transition layer and a molybdenum disulfide / silver composite layer in sequence on the surface of a nuclear energy component serving as a substrate, thereby forming a molybdenum disulfide composite coating; wherein the target materials used in the six-target co-sputtering technology include a silver target, two molybdenum disulfide targets, a titanium target and two molybdenum disulfide targets arranged in sequence in a counterclockwise direction, and the rotation speed of the sample holder fixing the nuclear energy component during the deposition of the molybdenum disulfide composite coating is 5 rpm.

[0035] Furthermore, the preparation method of the molybdenum disulfide composite coating specifically includes:

[0036] The unbalanced magnetron sputtering technology is combined with the six-target co-sputtering technology. The titanium target is used as the cathode target material, the inert gas is used as the working gas, the target current is applied to the titanium target, and the negative bias is applied to the substrate, so as to deposit a titanium transition layer on the substrate surface. The target current is 3.0-5.0A, the substrate bias is -50-100V, the working gas flow rate is 12-16seem, the substrate temperature is 80-120℃, and the pressure in the reaction chamber is 1.0-3.0×10 -3 torr, deposition time is 600-1800s;

[0037] The invention adopts unbalanced magnetron sputtering technology combined with six-target co-sputtering technology, takes titanium target, molybdenum disulfide target and silver as cathode target materials, takes inert gas as working gas, applies target current to titanium target, molybdenum disulfide target and tungsten carbide target, applies negative bias voltage to substrate, so as to deposit titanium / molybdenum disulfide / silver gradient transition layer on the surface of the titanium transition layer; wherein, the target current applied to the titanium target gradually decreases from 3.0 to 5.0 A to 0, the target current applied to the molybdenum disulfide target gradually increases from 0 to 1.6 A, the target current applied to the silver target gradually increases from 0 to 0.1 to 0.4 A, the substrate bias voltage is -50 to -70 V, the flow rate of working gas is 12 to 16 seem, the substrate temperature is 80 to 120 ° C, and the pressure of the reaction chamber is 1.0 to 3.0×10 -3 torr, deposition time is 1200-1800s;

[0038] And, unbalanced magnetron sputtering technology is combined with six-target co-sputtering technology, a molybdenum disulfide target and a silver target are used as cathode targets, an inert gas is used as a working gas, a target current is applied to the molybdenum disulfide target and the silver target, and a negative bias is applied to the substrate, so as to deposit a molybdenum disulfide / silver composite layer on the surface of the titanium / molybdenum disulfide / silver gradient transition layer; wherein the target current applied to the molybdenum disulfide target is 1.6A, the target current applied to the silver target is 0.1-0.4A, the substrate bias is -50--70V, the flow rate of the working gas is 12-16sccm, the substrate temperature is 80-120°C, and the pressure of the reaction chamber is 1.0-3.0x10 - 3 torr, and the deposition time is 6000 to 8000 s.

[0039] Further, the inert gas includes argon, but is not limited thereto.

[0040] Another aspect of an embodiment of the present invention also provides a molybdenum disulfide composite coating (denoted as; MoS2 / Ag composite coating), which includes a titanium transition layer, a titanium / molybdenum disulfide / silver gradient transition layer and a molybdenum disulfide / silver composite layer stacked in sequence in the thickness direction of the molybdenum disulfide composite coating; wherein, in the molybdenum disulfide / silver composite layer, silver is uniformly distributed in the molybdenum disulfide in the form of nanoparticles.

[0041] In some preferred embodiments, in a direction gradually moving away from the titanium transition layer, the titanium content in the titanium / molybdenum disulfide / silver gradient transition layer gradually decreases, the molybdenum disulfide content gradually increases, and the silver content gradually increases.

[0042] In some preferred embodiments, the silver in the molybdenum disulfide / silver composite layer is uniformly distributed in the molybdenum disulfide in the form of nanoparticles with a particle size of 10 to 200 nm.

[0043] In some preferred embodiments, the atomic content of silver in the molybdenum disulfide / silver composite layer is 4 to 8 at %.

[0044] In some preferred embodiments, the thickness of the molybdenum disulfide composite coating is 1.9 to 3.2 μm.

[0045] In some preferred embodiments, the thickness of the titanium transition layer is 100-300 nm.

[0046] In some preferred embodiments, the thickness of the titanium / molybdenum disulfide / silver gradient transition layer is 100-400 nm.

[0047] In some preferred embodiments, the thickness of the molybdenum disulfide / silver composite layer is 1.7-2.5 μm.

[0048] In some preferred embodiments, the molybdenum disulfide composite coating has an average friction coefficient of less than 0.03 and a wear rate of less than 2×10 -7 mm 3 / N·m.

[0049] In some preferred embodiments, the average friction coefficient of the molybdenum disulfide composite coating in an argon environment of 100 mbar is less than 0.065, and the wear rate is less than 2.1×10 -7 mm 3 / N·m.

[0050] Another aspect of an embodiment of the present invention further provides a method for preparing the aforementioned molybdenum disulfide composite coating, which comprises: using unbalanced magnetron sputtering technology in combination with six-target co-sputtering technology to sequentially deposit a titanium transition layer, a titanium / molybdenum disulfide / silver gradient transition layer and a molybdenum disulfide / silver composite layer on the surface of a nuclear energy component as a substrate, thereby forming a molybdenum disulfide composite coating; wherein the target materials used in the six-target co-sputtering technology include a silver target, two molybdenum disulfide targets, a titanium target and two molybdenum disulfide targets arranged in sequence in a counterclockwise direction, and the rotation speed of the sample holder fixing the nuclear energy component during the deposition of the molybdenum disulfide composite coating is 5 rpm.

[0051] In some preferred embodiments, the preparation method specifically comprises:

[0052] The unbalanced magnetron sputtering technology is combined with the six-target co-sputtering technology. The titanium target is used as the cathode target material, the inert gas is used as the working gas, the target current is applied to the titanium target, and the negative bias is applied to the substrate, so as to deposit a titanium transition layer on the substrate surface. The target current is 3.0-5.0A, the substrate bias is -50-100V, the working gas flow rate is 12-16sccm, the substrate temperature is 80-120℃, and the pressure in the reaction chamber is 1.0-3.0×10 -3torr, deposition time is 600-1800s;

[0053] The unbalanced magnetron sputtering technology is combined with the six-target co-sputtering technology, titanium target, molybdenum disulfide target and silver are used as cathode target materials, inert gas is used as working gas, target current is applied to the titanium target, molybdenum disulfide target and tungsten carbide target, and negative bias is applied to the substrate, so as to deposit a titanium / molybdenum disulfide / silver gradient transition layer on the surface of the titanium transition layer; wherein the target current applied to the titanium target gradually decreases from 3.0 to 5.0 A to 0, the target current applied to the molybdenum disulfide target gradually increases from 0 to 1.6 A, the target current applied to the silver target gradually increases from 0 to 0.1 to 0.4 A, the substrate bias is -50 to -70 V, the flow rate of the working gas is 12 to 16 sccm, the substrate temperature is 80 to 120 ° C, and the pressure of the reaction chamber is 1.0 to 3.0×10 -3 torr, deposition time is 1200-1800s;

[0054] And, unbalanced magnetron sputtering technology is combined with six-target co-sputtering technology, a molybdenum disulfide target and a silver target are used as cathode target materials, an inert gas is used as a working gas, a target current is applied to the molybdenum disulfide target and the silver target, and a negative bias is applied to the substrate, so that a molybdenum disulfide / silver composite layer is deposited on the surface of the titanium / molybdenum disulfide / silver gradient transition layer; wherein the target current applied to the molybdenum disulfide target is 1.6A, the target current applied to the silver target is 0.1-0.4A, the substrate bias is -50--70V, the flow rate of the working gas is 12-16sccm, the substrate temperature is 80-120°C, and the pressure of the reaction chamber is 1.0-3.0×10 - 3 torr, and the deposition time is 6000 to 8000 s.

[0055] Further, the inert gas includes argon, but is not limited thereto.

[0056] Furthermore, the preparation method further comprises: evacuating the reaction chamber to a predetermined vacuum degree (3×10 -5 torr or less), the substrate surface is subjected to plasma etching to remove the oxide on the substrate surface; the specific etching method includes applying a bias voltage of -400 to -500 V to the substrate, etching the substrate at a temperature of 100 to 150° C., and etching for 1200 to 1800 seconds.

[0057] Furthermore, the substrate material is not limited and may be a single crystal silicon wafer, and / or 316L stainless steel, and / or 9Cr18 and / or T6AL4V, etc., but is not limited thereto.

[0058] The inventors of this case also conducted the following performance tests on the molybdenum disulfide composite coating obtained in the above-mentioned best embodiment:

[0059] The friction and wear test in the atmospheric environment was conducted using an Anton Paar friction and wear tester. The friction and wear performance of the coating was analyzed in a 100 mbar oxygen environment and a 100 mbar argon environment at a test temperature of 25 ± 3 ° C. A 9Cr18 steel ball was used as the friction pair, and a reciprocating sliding mode was adopted with a frequency of 5 Hz, a sliding step length of 5 mm, a running time of 1 h, and a normal load of 5 N. A contact step profile was used to measure the cross-section of the wear area, and the wear volume of the coating was calculated by multiplying it by the sliding step length. The wear rate was obtained by dividing the wear volume by the load and the total sliding distance.

[0060] Test results:

[0061] The molybdenum disulfide composite coating provided by the present invention has an average friction coefficient of less than 0.03 in an oxygen environment of 100 mbar, and a wear rate of less than 2×10 -7 mm 3 / N·m, the average friction coefficient in 100mbar argon environment is below 0.065, and the wear rate is less than 2.1×10 -7 mm 3 / N·m. In summary, by means of the above technical solution, the composite coating provided by the present invention exhibits low friction and wear performance in an oxygen environment and an argon environment, and can meet the long-life and reliable service requirements of nuclear power mechanical motion devices.

[0062] The technical solution of the present invention is further described in detail below in conjunction with several preferred embodiments and drawings. This embodiment is implemented on the premise of the technical solution of the invention, and a detailed implementation method and specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments.

[0063] Unless otherwise specified, the experimental materials used in the following examples can be purchased from conventional biochemical reagent companies.

[0064] Example 1

[0065] In this embodiment, the substrate material is 316L stainless steel or single crystal silicon wafer. The MoS2 / Ag composite coating (0.4A) is prepared on the substrate surface by unbalanced magnetron sputtering technology, which mainly includes the following steps:

[0066] The substrate surface was mechanically polished, and the substrate material was placed in an acetone solution for ultrasonic cleaning for 15 minutes, dried with nitrogen, placed in an anhydrous ethanol solution for ultrasonic cleaning for 15 minutes, and dried with nitrogen.

[0067] The targets were arranged in a counterclockwise direction: one Ag target (purity 99.9 at.%), two MoS2 targets (purity 99.9 at.%), one Ti target (purity 99.9 at.%), and two MoS2 targets (purity 99.9 at.%).

[0068] The cleaned substrate was placed in an unbalanced magnetron sputtering chamber and evacuated to a vacuum degree of less than 3×10 - 5 torr, high-purity argon gas was filled into the chamber, and then the target was cleaned by argon plasma sputtering for 30 minutes. The substrate temperature was 100-120°C, and the sample holder speed was set to 5 rpm to prepare and deposit MoS2 / Ag composite coating. The specific steps are as follows: Unbalanced magnetron sputtering technology was used, and the specific steps are as follows:

[0069] Plasma etching, a bias voltage of -500 V was applied to the substrate, the program running time was 30 min, and the substrate temperature was 100 °C.

[0070] The titanium transition layer was deposited with a titanium target sputtering current of 5.0 A, a substrate bias of -70 V, an Ar gas, a gas flow of 16 sccm, a deposition substrate temperature of 80 °C, and a pressure of 1.3 × 10 -3 torr, the deposition time was 1200s, and a titanium transition layer with a thickness of about 100nm was deposited on the substrate surface;

[0071] The titanium / molybdenum disulfide / silver gradient transition layer was deposited. The titanium target current was gradually reduced from 5.0A to 0, the target current of the molybdenum disulfide target was gradually increased to 1.6A, and the target current applied to the silver target was gradually increased to 0.4A. The substrate bias voltage was -50 to -70V, the working gas flow rate was 16sccm, the substrate temperature was 80 to 120℃, and the reaction chamber pressure was 1.3×10 -3 torr, the deposition time is 1800s, and then a titanium / molybdenum disulfide / silver gradient transition layer is deposited on the surface of the titanium transition layer, and the thickness of the transition layer is controlled between 100nm;

[0072] Deposit a MoS2 / Ag composite layer, maintaining the MoS2 target sputtering current at 1.6 A and the Ag target sputtering current at 0.4 A, until the total thickness of the composite coating deposited reaches 2.6 μm.

[0073] The MoS2 / Ag composite coating (0.4A) obtained after the above deposition treatment was subjected to the following structural performance tests:

[0074] (1) Structural test:

[0075] The XRD results of the composite coating are as follows: Figure 1 As shown, the coating preferentially grows in the MoS2(002) orientation.

[0076] (2) Morphology test:

[0077] The cross-sectional SEM of the MoS2 / Ag composite coating (0.4A) is as follows Figure 2As shown, the thickness of the titanium transition layer is about 100 nm, the thickness of the titanium / molybdenum disulfide / silver gradient transition layer is about 150 nm, and the total thickness of the MoS2 / Ag composite coating is about 2.6 μm. Furthermore, the cross-sectional morphology of the coating is dense.

[0078] The surface SEM image of the MoS2 / Ag composite coating (0.4A) is as follows Figure 3 As shown, further, the coating surface is flat.

[0079] The structural TEM image of the MoS2 / Ag composite coating (0.4A) is shown in Figure 4 As shown, further, the soft metal silver is uniformly distributed in the coating in the form of nanoparticles of 10 to 200 nm.

[0080] (3) Atmosphere friction and wear test:

[0081] The friction and wear performance of the coating was analyzed in an Anton Paar friction and wear tester at a test temperature of 25±3°C in an oxygen environment of 100mbar and an argon environment of 100mbar. A 9Cr18 steel ball was used as the friction pair, a reciprocating sliding mode was adopted, a frequency of 5Hz, a sliding step of 5mm, a running time of 1h, and a normal load of 5N.

[0082] The average friction coefficient of the MoS2 / Ag composite coating in an oxygen environment is about 0.027, and the wear rate is about 1.64×10 -7 mm 3 / N·m; the average friction coefficient in argon environment at 100mbar is about 0.063, and the wear rate is about 1.84x10 - 7 mm 3 / N·m.

[0083] Figure 7 is a friction coefficient curve of the MoS2 / Ag composite coating (0.4A) prepared in Example 1 of the present invention in an oxygen environment of 100 mbar; Figure 8 It is a friction coefficient curve of the MoS2 / Ag composite coating (0.4A) prepared in Example 1 of the present invention in an argon environment of 100 mbar.

[0084] Example 2

[0085] In this embodiment, the substrate material is 316L stainless steel or single crystal silicon wafer. The MoS2 / Ag composite coating (0.3A) is prepared on the substrate surface by using unbalanced magnetron sputtering technology, which mainly includes the following steps:

[0086] The substrate surface was mechanically polished, and the substrate material was placed in an acetone solution for ultrasonic cleaning for 15 minutes, dried with nitrogen, placed in an anhydrous ethanol solution for ultrasonic cleaning for 15 minutes, and dried with nitrogen.

[0087] The targets were arranged in a counterclockwise direction: one Ag target (purity 99.9 at.%), two MoS2 targets (purity 99.9 at.%), one Ti target (purity 99.9 at.%), and two MoS2 targets (purity 99.9 at.%).

[0088] The cleaned substrate was placed in an unbalanced magnetron sputtering chamber and evacuated to a vacuum degree of less than 3×10 - 5 torr, high-purity argon gas was filled into the chamber, and then the target was cleaned by argon plasma sputtering for 30 minutes. The substrate temperature was 100-120°C, and the sample holder speed was set to 5 rpm to prepare and deposit MoS2 / Ag composite coating (0.3A). The specific steps are as follows: Unbalanced magnetron sputtering technology was used, and the specific steps are as follows:

[0089] Plasma etching, a bias voltage of -500 V was applied to the substrate, the program running time was 30 min, and the substrate temperature was 100 °C.

[0090] The titanium transition layer was deposited with a titanium target sputtering current of 5.0 A, a substrate bias of -70 V, an Ar gas, a gas flow of 16 sccm, a deposition substrate temperature of 80 °C, and a pressure of 1.3 × 10 -3 torr, the deposition time was 1200s, and a titanium transition layer with a thickness of about 100nm was deposited on the substrate surface;

[0091] The titanium / molybdenum disulfide / silver gradient transition layer was deposited. The titanium target current was gradually reduced from 5.0A to 0, the target current of the molybdenum disulfide target was gradually increased to 1.6A, and the target current applied to the silver target was gradually increased to 0.3A. The substrate bias voltage was -50 to -70V, the working gas flow rate was 16sccm, the substrate temperature was 80 to 120°C, and the reaction chamber pressure was 1.3×10 -3 torr, the deposition time is 1800s, and then a titanium / molybdenum disulfide / silver gradient transition layer is deposited on the surface of the titanium transition layer, and the thickness of the transition layer is controlled between 100nm;

[0092] The MoS2 / Ag composite layer was deposited, and the MoS2 target sputtering current was maintained at 1.6 A and the Ag target sputtering current was maintained at 0.3 A, until the total thickness of the composite coating deposited reached 2.9 μm.

[0093] The specific composition parameters of the prepared MoS2 / Ag composite coating (0.3A) are shown in Table 1.

[0094] The MoS2 / Ag composite coating (0.3A) obtained after the above deposition treatment was subjected to atmosphere friction and wear tests. The friction and wear performance of the coating was analyzed in an Anton Paar friction and wear tester at a test temperature of 25±3°C in an oxygen environment of 100mbar and an argon environment of 100mbar. A 9Cr18 steel ball was used as the friction pair, a reciprocating sliding mode was adopted, a frequency of 5Hz, a sliding step of 5mm, a running time of 1h, and a normal load of 5N.

[0095] The average friction coefficients of the MoS2 / Ag composite coating (0.3A) under oxygen and argon are shown in Table 1. The average friction coefficient in oxygen environment is about 0.028, and the wear rate is about 1.81×10 -7 mm 3 / N·m; the average friction coefficient in argon environment at 100mbar is about 0.059, and the wear rate is about 1.96×10 -7 mm 3 / N·m.

[0096] Example 3

[0097] In this embodiment, the substrate material is 316L stainless steel or single crystal silicon wafer. The MoS2 / Ag composite coating (0.1A) is prepared on the substrate surface by using unbalanced magnetron sputtering technology, which mainly includes the following steps:

[0098] The substrate surface was mechanically polished, and the substrate material was placed in an acetone solution for ultrasonic cleaning for 15 minutes, dried with nitrogen, placed in an anhydrous ethanol solution for ultrasonic cleaning for 15 minutes, and dried with nitrogen.

[0099] The targets were arranged in a counterclockwise direction: one Ag target (purity 99.9 at.%), two MoS2 targets (purity 99.9 at.%), one Ti target (purity 99.9 at.%), and two MoS2 targets (purity 99.9 at.%).

[0100] The cleaned substrate was placed in an unbalanced magnetron sputtering chamber and evacuated to a vacuum degree of less than 3×10 - 5 torr, high-purity argon gas was filled into the chamber, and then the target was cleaned by argon plasma sputtering for 30 minutes. The substrate temperature was 100-120°C, and the sample holder speed was set to 5 rpm to prepare and deposit MoS2 / Ag composite coating (0.1A). The specific steps are as follows: Unbalanced magnetron sputtering technology was used, and the specific steps are as follows:

[0101] Plasma etching, a bias voltage of -500 V was applied to the substrate, the program running time was 30 min, and the substrate temperature was 100 °C.

[0102] The titanium transition layer was deposited with a titanium target sputtering current of 5.0 A, a substrate bias of -70 V, an Ar gas, a gas flow of 16 sccm, a deposition substrate temperature of 80 °C, and a pressure of 1.3 × 10 -3 torr, the deposition time was 1200s, and a titanium transition layer with a thickness of about 100nm was deposited on the substrate surface;

[0103] The titanium / molybdenum disulfide / silver gradient transition layer was deposited. The titanium target current was gradually reduced from 5.0A to 0, the target current of the molybdenum disulfide target was gradually increased to 1.6A, and the target current applied to the silver target was gradually increased to 0.1A. The substrate bias voltage was -50 to -70V, the working gas flow rate was 16sccm, the substrate temperature was 80 to 120°C, and the reaction chamber pressure was 1.3×10 -3 torr, the deposition time is 1800s, and then a titanium / molybdenum disulfide / silver gradient transition layer is deposited on the surface of the titanium transition layer, and the thickness of the transition layer is controlled between 100nm;

[0104] Deposit a MoS2 / Ag composite layer, maintaining the MoS2 target sputtering current at 1.6 A and the Ag target sputtering current at 0.1 A, until the total thickness of the composite coating deposited reaches 2.4 μm.

[0105] The MoS2 / Ag composite coating (0.1A) obtained after the above deposition treatment was subjected to atmosphere friction and wear test. The friction and wear performance of the coating was analyzed in an oxygen environment of 100 mbar and an argon environment of 100 mbar, respectively, using an Anton Paar friction and wear tester at a test temperature of 25±3°C. A 9Cr18 steel ball was used as the friction pair, a reciprocating sliding mode was adopted, a frequency of 5 Hz, a sliding step of 5 mm, a running time of 1 h, and a normal load of 5 N.

[0106] The average friction coefficients of the MoS2 / Ag composite coating (0.1A) under oxygen and argon are shown in Table 1. The average friction coefficient in oxygen environment is about 0.027, and the wear rate is about 1.98×10 -7 mm 3 / N·m; the average friction coefficient in argon environment at 100mbar is about 0.064, and the wear rate is about 2.04×10 -7 mm 3 / N·m.

[0107] Comparative Example 1

[0108] The difference between this comparative example and Example 1 is that soft metal silver is not introduced into the MoS2 coating. In this comparative example, the substrate material is a single crystal silicon wafer or 316L stainless steel. The MoS2 coating is prepared on the substrate surface by using unbalanced magnetron sputtering technology, which mainly includes the following steps:

[0109] The substrate surface was mechanically polished, and the substrate material was placed in an acetone solution for ultrasonic cleaning for 15 minutes, dried with nitrogen, placed in an anhydrous ethanol solution for ultrasonic cleaning for 15 minutes, and dried with nitrogen.

[0110] The cleaned substrate was placed in an unbalanced magnetron sputtering chamber and evacuated to a vacuum degree of less than 3×10 - 3 torr, and then sputter clean the target for 30 minutes, with the substrate temperature at 100-150°C.

[0111] To prepare and deposit the MoS2 coating, the chamber is filled with high-purity argon gas, and a Ti target (purity of 99.99 at.%) and a MoS2 target (purity of 99.9 at.%) are used for the control setting, and the unbalanced magnetron sputtering technology is used. The specific steps are as follows:

[0112] For plasma etching, a bias voltage of -500 V was applied to the substrate, the program running time was 30 min, and the substrate temperature was 150 °C.

[0113] The titanium target sputtering current was 5.0A, the substrate bias voltage was -70V, the working gas was Ar, the gas flow rate was 16sccm, the substrate temperature was 120℃, and the pressure was 1.3×10 -3 torr, the deposition time was 1200s, and a titanium transition layer with a thickness of about 200nm was deposited on the substrate surface;

[0114] The sputtering current of the titanium target was gradually reduced to 0, and the sputtering current of the molybdenum disulfide target was gradually increased to 1.6 A. The working gas was Ar, the gas flow rate was 16 sccm, the substrate bias was -70 V, the deposition substrate temperature was 110 °C, and the pressure was 1.3 × 10 -3 torr, the deposition time is 1800s, and the thickness of the titanium / molybdenum disulfide gradient transition layer deposited on the surface of the titanium transition layer is about 200nm;

[0115] The sputtering current of the molybdenum disulfide target was maintained at 1.6 A and the deposition time was 7000 s until the MoS2 coating thickness reached 2.7 μm.

[0116] The molybdenum disulfide coating obtained after the above deposition treatment was subjected to the following structural performance tests:

[0117] (1) Structural test:

[0118] The XRD results of the MoS2 coating are as follows Figure 1 As shown, the diffraction peak intensity of MoS2 (002) crystal plane of MoS2 coating is obviously lower.

[0119] (2) Morphology test:

[0120] The cross-sectional SEM of the coating is as follows Figure 5 As shown, the thickness of the Ti transition layer is about 200nm, the thickness of the Ti / MoS2 gradient transition layer is about 200nm, and the thickness of MoS2 is about 1.6μm. The total thickness of the MoS2 coating is about 2.7μm. Furthermore, the cross-sectional morphology of the coating is loose and exhibits typical columnar crystals.

[0121] The surface SEM image of the coating is as follows Figure 6 As shown, further, the surface morphology of the coating is not smooth.

[0122] (3) Atmosphere friction and wear test:

[0123] The friction and wear performance of the coating was analyzed in an Anton Paar friction and wear tester at a test temperature of 25±3°C in an oxygen environment of 100mbar and an argon environment of 100mbar. A 9Cr18 steel ball was used as the friction pair, a reciprocating sliding mode was adopted, a frequency of 5Hz, a sliding step of 5mm, a running time of 1h, and a normal load of 5N.

[0124] The average friction coefficient of the MoS2 coating in an oxygen environment is about 0.047, and the wear rate is about 2.01×10 -7 mm 3 / N·m; the average friction coefficient in argon environment at 100mbar is about 0.068, and the wear rate is about 3.70×10 -7 mm 3 / N·m.

[0125] Comparative Example 2

[0126] Compared with Example 1, the difference between this comparative example and Example 1 is that the silver in the molybdenum disulfide / silver composite layer is not uniformly distributed in the molybdenum disulfide in the form of nanoparticles with a particle size of 10 to 200 nm. In this comparative example, the substrate material is a single crystal silicon wafer or 316L stainless steel. The MoS2 / Ag composite coating is prepared on the substrate surface by unbalanced magnetron sputtering technology (1.5 rpm), which mainly includes the following steps:

[0127] The substrate surface was mechanically polished, and the substrate material was placed in an acetone solution for ultrasonic cleaning for 15 minutes, dried with nitrogen, placed in an anhydrous ethanol solution for ultrasonic cleaning for 15 minutes, and dried with nitrogen.

[0128] The targets were arranged in a counterclockwise direction: one Ag target (purity 99.9 at.%), two MoS2 targets (purity 99.9 at.%), one Ti target (purity 99.9 at.%), and two MoS2 targets (purity 99.9 at.%).

[0129] The cleaned substrate was placed in an unbalanced magnetron sputtering chamber, evacuated to a vacuum degree of less than 3×10-5torr, and the chamber was filled with high-purity argon gas. Then, the target was sputtered and cleaned for 30 minutes using argon plasma. The substrate temperature was 100-120°C, and the sample holder speed was set to 1.5 rpm. The MoS2 / Ag composite coating was deposited (1.5 rpm). The specific steps are as follows: Using unbalanced magnetron sputtering technology, the specific steps are as follows:

[0130] Plasma etching, a bias voltage of -500 V was applied to the substrate, the program running time was 30 min, and the substrate temperature was 100 °C.

[0131] The titanium transition layer was deposited with a titanium target sputtering current of 5.0 A, a substrate bias of -70 V, an Ar gas, a gas flow of 16 sccm, a deposition substrate temperature of 80 °C, and a pressure of 1.3 × 10 -3 torr, the deposition time was 1200 s, the sample holder speed was set to 1.5 rpm, and a titanium transition layer with a thickness of about 100 nm was deposited on the substrate surface;

[0132] The titanium / molybdenum disulfide / silver gradient transition layer was deposited. The titanium target current was gradually reduced from 5.0A to 0, the target current of the molybdenum disulfide target was gradually increased to 1.6A, and the target current applied to the silver target was gradually increased to 0.4A. The substrate bias voltage was -50 to -70V, the working gas flow rate was 16sccm, the substrate temperature was 80 to 120℃, and the reaction chamber pressure was 1.3×10 -3 torr, the deposition time was 1800s, the sample holder speed was set to 1.5 rpm, and then a titanium / molybdenum disulfide / silver gradient transition layer was deposited on the surface of the titanium transition layer, and the thickness of the transition layer was controlled between 100nm;

[0133] Deposit the MoS2 / Ag composite layer, set the sample holder speed to 1.5 rpm, maintain the MoS2 target sputtering current at 1.6 A and the Ag target sputtering current at 0.4 A, until the total thickness of the composite coating deposited reaches 2.8 μm.

[0134] The MoS2 / Ag composite coating (1.5 rpm) obtained after the above deposition treatment was subjected to atmosphere friction and wear test. The friction and wear performance of the coating was analyzed in 100 mbar oxygen environment and 100 mbar argon environment respectively using Anton Paar friction and wear tester at a test temperature of 25±3°C. A 9Cr18 steel ball was used as the friction pair, a reciprocating sliding mode was adopted, a frequency of 5 Hz, a sliding step of 5 mm, a running time of 1 h, and a normal load of 5 N.

[0135] The average friction coefficient and wear rate of the MoS2 / Ag composite coating (1.5 rpm) under oxygen and argon are shown in Table 1. The average friction coefficient in oxygen environment is about 0.043, and the wear rate is about 2.29×10 -7 mm 3 / N·m; the average friction coefficient in argon environment at 100mbar is about 0.080, and the wear rate is about 5.08×10 -7 mm 3 / N·m.

[0136] The two coatings prepared by different processes in Examples 1-3 and Comparative Examples 1-2 are named as follows: MoS2 / Ag composite coating (0.4A), MoS2 / Ag composite coating (0.3A), MoS2 / Ag composite coating (0.1A), MoS2 coating, and MoS2 / Ag composite coating (1.5 rpm).

[0137] The average friction coefficients of the coatings in Examples 1-3 and Comparative Examples 1-2 in an oxygen environment of 100 mbar and an argon environment of 100 mbar are shown in Table 1.

[0138] Table 1: Average friction coefficient of coating samples under oxygen and argon

[0139]

[0140] It can be seen from Table 1 that the deposited MoS2 / Ag composite coating has the lowest friction coefficient and wear rate in both 100 mbar oxygen environment and 100 mbar argon environment.

[0141] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.

[0142] It should be understood that the technical solution of the present invention is not limited to the above-mentioned specific implementation cases. Any technical deformation made according to the technical solution of the present invention without departing from the scope of protection of the purpose of the present invention and the claims shall fall within the protection scope of the present invention.

Claims

1. Use of molybdenum disulfide composite coating in surface protection of nuclear energy components in oxygen or argon, characterized in that: The molybdenum disulfide composite coating comprises a titanium transition layer, a titanium / molybdenum disulfide / silver gradient transition layer and a molybdenum disulfide / silver composite layer which are sequentially stacked in the thickness direction of the molybdenum disulfide composite coating; wherein, in the molybdenum disulfide / silver composite layer, silver is uniformly distributed in the molybdenum disulfide in the form of nanoparticles.

2. The use according to claim 1, characterized in that: In a direction gradually moving away from the titanium transition layer, the titanium content in the titanium / molybdenum disulfide / silver gradient transition layer gradually decreases, the molybdenum disulfide content gradually increases, and the silver content gradually increases; And / or, the silver in the molybdenum disulfide / silver composite layer is uniformly distributed in the molybdenum disulfide in the form of nanoparticles with a particle size of 10 to 200 nm / mm; and / or, the atomic content of silver in the molybdenum disulfide / silver composite layer is 4 to 8 at %; And / or, the thickness of the molybdenum disulfide composite coating is 1.9 to 3.2 μm; and / or, the thickness of the titanium transition layer is 100 to 300 nm; and / or, the thickness of the titanium / molybdenum disulfide / silver gradient transition layer is 100 to 400 nm; and / or, the thickness of the molybdenum disulfide / silver composite layer is 1.7 to 2.5 μm.

3. The use according to claim 1, characterized in that: The average friction coefficient of the molybdenum disulfide composite coating in an oxygen environment of 100 mbar is less than 0.03, and the wear rate is less than 2×10 -7 mm 3 / N·m; And / or, the average friction coefficient of the molybdenum disulfide composite coating in an argon environment of 100 mbar is less than 0.065, and the wear rate is less than 2.1×10 -7 mm 3 / N·m.

4. The use according to claim 1, characterized in that The preparation method of the molybdenum disulfide composite coating comprises: An unbalanced magnetron sputtering technology is combined with a six-target co-sputtering technology to sequentially deposit a titanium transition layer, a titanium / molybdenum disulfide / silver gradient transition layer and a molybdenum disulfide / silver composite layer on the surface of a nuclear energy component as a substrate, thereby forming a molybdenum disulfide composite coating; wherein the target materials used in the six-target co-sputtering technology include a silver target, two molybdenum disulfide targets, a titanium target and two molybdenum disulfide targets arranged in sequence in a counterclockwise direction, and the rotation speed of a sample holder fixing the nuclear energy component during the deposition of the molybdenum disulfide composite coating is 5 rpm.

5. The use according to claim 4, characterized in that The preparation method of the molybdenum disulfide composite coating specifically comprises: The unbalanced magnetron sputtering technology is combined with the six-target co-sputtering technology. The titanium target is used as the cathode target material, the inert gas is used as the working gas, the target current is applied to the titanium target, and the negative bias is applied to the substrate, so as to deposit a titanium transition layer on the substrate surface. The target current is 3.0-5.0A, the substrate bias is -50-100V, the working gas flow rate is 12-16sccm, the substrate temperature is 80-120℃, and the pressure in the reaction chamber is 1.0-3.0×10 -3 torr, deposition time is 600-1800s; The unbalanced magnetron sputtering technology is combined with the six-target co-sputtering technology, titanium target, molybdenum disulfide target and silver are used as cathode target materials, inert gas is used as working gas, target current is applied to the titanium target, molybdenum disulfide target and tungsten carbide target, and negative bias is applied to the substrate, so as to deposit a titanium / molybdenum disulfide / silver gradient transition layer on the surface of the titanium transition layer; wherein the target current applied to the titanium target gradually decreases from 3.0 to 5.0 A to 0, the target current applied to the molybdenum disulfide target gradually increases from 0 to 1.6 A, the target current applied to the silver target gradually increases from 0 to 0.1 to 0.4 A, the substrate bias is -50 to -70 V, the flow rate of the working gas is 12 to 16 sccm, the substrate temperature is 80 to 120 ° C, and the pressure of the reaction chamber is 1.0 to 3.0×10 -3 torr, deposition time is 1200-1800s; And, unbalanced magnetron sputtering technology is combined with six-target co-sputtering technology, a molybdenum disulfide target and a silver target are used as cathode target materials, an inert gas is used as a working gas, a target current is applied to the molybdenum disulfide target and the silver target, and a negative bias is applied to the substrate, so that a molybdenum disulfide / silver composite layer is deposited on the surface of the titanium / molybdenum disulfide / silver gradient transition layer; wherein the target current applied to the molybdenum disulfide target is 1.6A, the target current applied to the silver target is 0.1-0.4A, the substrate bias is -50--70V, the flow rate of the working gas is 12-16sccm, the substrate temperature is 80-120°C, and the pressure of the reaction chamber is 1.0-3.0×10 -3 torr, and the deposition time is 6000 to 8000 s.

6. A molybdenum disulfide composite coating, characterized in that: It comprises a titanium transition layer, a titanium / molybdenum disulfide / silver gradient transition layer and a molybdenum disulfide / silver composite layer which are sequentially stacked in the thickness direction of the molybdenum disulfide composite coating; wherein the silver in the molybdenum disulfide / silver composite layer is uniformly distributed in the molybdenum disulfide in the form of nanoparticles.

7. The molybdenum disulfide composite coating according to claim 6, characterized in that: In a direction gradually moving away from the titanium transition layer, the titanium content in the titanium / molybdenum disulfide / silver gradient transition layer gradually decreases, the molybdenum disulfide content gradually increases, and the silver content gradually increases; And / or, the silver in the molybdenum disulfide / silver composite layer is uniformly distributed in the molybdenum disulfide in the form of nanoparticles with a particle size of 10 to 200 nm; and / or, the atomic content of silver in the molybdenum disulfide / silver composite layer is 4 to 8 at %; And / or, the thickness of the molybdenum disulfide composite coating is 1.9 to 3.2 μm; and / or, the thickness of the titanium transition layer is 100 to 300 nm; and / or, the thickness of the titanium / molybdenum disulfide / silver gradient transition layer is 100 to 400 nm; and / or, the thickness of the molybdenum disulfide / silver composite layer is 1.7 to 2.5 μm.

8. The molybdenum disulfide composite coating according to claim 6, characterized in that: The average friction coefficient of the molybdenum disulfide composite coating in an oxygen environment of 100 mbar is less than 0.03, and the wear rate is less than 2×10 -7 mm 3 / N·m; And / or, the average friction coefficient of the molybdenum disulfide composite coating in an argon environment of 100 mbar is less than 0.065, and the wear rate is less than 2.1×10 -7 mm 3 / N·m.

9. The method for preparing the molybdenum disulfide composite coating according to any one of claims 6 to 8, characterized in that: include: An unbalanced magnetron sputtering technology is combined with a six-target co-sputtering technology to sequentially deposit a titanium transition layer, a titanium / molybdenum disulfide / silver gradient transition layer and a molybdenum disulfide / silver composite layer on the surface of a nuclear energy component as a substrate, thereby forming a molybdenum disulfide composite coating; wherein the target materials used in the six-target co-sputtering technology include a silver target, two molybdenum disulfide targets, a titanium target and two molybdenum disulfide targets arranged in sequence in a counterclockwise direction, and the rotation speed of a sample holder fixing the nuclear energy component during the deposition of the molybdenum disulfide composite coating is 5 rpm.

10. The preparation method according to claim 9, characterized in that: Specifically include: The unbalanced magnetron sputtering technology is combined with the six-target co-sputtering technology. The titanium target is used as the cathode target material, the inert gas is used as the working gas, the target current is applied to the titanium target, and the negative bias is applied to the substrate, so as to deposit a titanium transition layer on the substrate surface. The target current is 3.0-5.0A, the substrate bias is -50-100V, the working gas flow rate is 12-16sccm, the substrate temperature is 80-120℃, and the pressure in the reaction chamber is 1.0-3.0×10 -3 torr, deposition time is 600-1800s; The unbalanced magnetron sputtering technology is combined with the six-target co-sputtering technology, titanium target, molybdenum disulfide target and silver are used as cathode target materials, inert gas is used as working gas, target current is applied to the titanium target, molybdenum disulfide target and tungsten carbide target, and negative bias is applied to the substrate, so as to deposit a titanium / molybdenum disulfide / silver gradient transition layer on the surface of the titanium transition layer; wherein the target current applied to the titanium target gradually decreases from 3.0 to 5.0 A to 0, the target current applied to the molybdenum disulfide target gradually increases from 0 to 1.6 A, the target current applied to the silver target gradually increases from 0 to 0.1 to 0.4 A, the substrate bias is -50 to -70 V, the flow rate of the working gas is 12 to 16 sccm, the substrate temperature is 80 to 120 ° C, and the pressure of the reaction chamber is 1.0 to 3.0×10 -3 torr, deposition time is 1200-1800s; And, unbalanced magnetron sputtering technology is combined with six-target co-sputtering technology, a molybdenum disulfide target and a silver target are used as cathode target materials, an inert gas is used as a working gas, a target current is applied to the molybdenum disulfide target and the silver target, and a negative bias is applied to the substrate, so that a molybdenum disulfide / silver composite layer is deposited on the surface of the titanium / molybdenum disulfide / silver gradient transition layer; wherein the target current applied to the molybdenum disulfide target is 1.6A, the target current applied to the silver target is 0.1-0.4A, the substrate bias is -50--70V, the flow rate of the working gas is 12-16sccm, the substrate temperature is 80-120°C, and the pressure of the reaction chamber is 1.0-3.0×10 -3 torr, and the deposition time is 6000 to 8000 s.

Citation Information

Patent Citations

  • Molybdenum disulfide silver-doped vulcanized film and preparation method and application thereof

    CN112210753A

Cited By

  • Molybdenum disulfide composite film and preparation method and application thereof

    CN121518995A